Анализ „природы” ностальгии в художественном пространстве кинокартины Андрея Тарковского Ностальгия - Królikiewicz, Natalia (Studia Rossica Posnaniensia, 2019)
The article concentrates on the penultimate work by Andrei Tarkovsky Nostalgia. It attempts at analyzing the nostalgia experienced by the main character as a longing for the Kingdom of Heaven. The interpretation of the artistic world of the film involved the comparative analysis of individual frames. Using this method revealed additional semantic fields and led to defining nostalgia as the possibility of uniting with God and the coming of the Kingdom of Heaven.